Influence of oral health on the quality of life of institutionalized and noninstitutionalized elderly people - Saliba, Tânia [UNESP]; Ortega, Mariana [UNESP]; Goya, Karimy [UNESP]; Moimaz, Suzely [UNESP]; Garbin, Cleá [UNESP] (Wolters Kluwer, 2018)
Background: This study aimed to determine the perception of institutionalized (G1) and noninstitutionalized (G2) elderly people on oral health and quality of life (QOL). Materials and Methods: This cross-sectional, exploratory study applied two instruments-the Geriatric Oral Health Assessment Index (GOHAI) and the World Health Organization QOL-Bref (WHOQOL-BREF)-in two cities of the state of Sao Paulo, Brazil. Among the institutionalized elderly, G1 (n = 150), 50% were not mentally able to answer the questions correctly, 12% did not answer all the questions, and 7.34% refused to take part in the research or were too frail or dependent, resulting in 31 institutionalized participants. In the noninstitutionalized group, G2 (n = 80), 52.50% refused to take part in the research, resulting in 38 noninstitutionalized participants. The elderly individuals (i) who did not respond to three or more questions of the GOHAI, (ii) those who did not answer all the questions of the WHOQOL-Bref, and (iii) those who did not consent to participate in the research study were excluded from the study population (P < 0.05 consider significant). Results: The oral health of both groups minimally affected the QOL of the elderly. The WHOQOL-Bref score varied between the two study groups mainly in terms of physical domain and self-perception of QOL. The study groups showed differences in some variables: Self-perception of QOL (P = 0.0209), mobility (P = 0.0057), and access to health services (P = 0.0252). G2 presented the best conditions. Conclusion: The oral health condition of both groups minimally affected the QOL of the participants; however, differences in the self-perception of QOL were significant, mainly in the physical domain.
Keywords: Ageing; eldery; oral health; people; quality of life